Optical laminate and image display device

By using an adhesive sheet made of a photocurable composition containing a monomer group and bonding it with a phase difference film, the image quality problem of image display device in a high-temperature environment, especially the problem of cracks in the phase difference film, and higher image quality and anchoring force are achieved.

CN119630995APending Publication Date: 2025-03-14NITTO DENKO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380055804.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-21
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Image display devices using photocurable adhesive sheets in high temperature environments are prone to image quality problems, especially the phase difference film is prone to cracks caused by changes in ambient temperature.

Method used

The adhesive sheet made of a photocurable composition formed of a partial polymer containing a monomer group and/or the above-mentioned monomer group is used, and the phase difference film is directly connected to the layer with a thickness of 10 μm or less, so as to ensure that the amount of residual monomer in the adhesive sheet is 16,000 ppm or less.

Benefits of technology

It effectively reduces the occurrence of phase difference film cracks in high-temperature environments, improves the image quality of the image display device, and enhances the anchoring force of the adhesive sheet to the phase difference film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630995A_ABST
    Figure CN119630995A_ABST
Patent Text Reader

Abstract

Provided is an optical laminate suitable for use in an image display device that may be exposed to a high-temperature environment. The provided optical laminate is provided with: an adhesive sheet comprising a photocurable composition containing a monomer group and / or a partial polymer of the monomer group; and a phase difference film. The adhesive sheet is in contact with the phase difference film directly or via a layer having a thickness of 10 [mu] m or less. The amount of residual monomers contained in the adhesive sheet is 16000 ppm (weight basis) or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical layered body and an image display device. Background Art

[0002] Various image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices generally have an optical laminate including an optical film such as a polarizing film and an adhesive sheet. Adhesive sheets are usually used for the bonding between the optical films contained in the optical laminate and the bonding between the optical laminate and the image display panel. As an adhesive sheet, a typical sheet is obtained by curing a monomer group including an acrylic monomer, a silicone monomer, etc. by polymerization and crosslinking. Patent document 1 discloses an adhesive sheet formed by a photocurable composition (hereinafter, "photocurable adhesive sheet"). As a different type, there is an adhesive sheet formed by curing a layer including an adhesive composition and a solvent by heat (hereinafter, "thermosetting adhesive sheet").

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-155981 Summary of the invention

[0006] Problems to be solved by the invention

[0007] Compared with the case of using a thermosetting adhesive sheet, when a photocurable adhesive sheet is used for an optical laminate, there is a tendency for image quality problems of the image display device to occur. Such problems are particularly likely to occur in image display devices such as those for use in vehicles and which may be exposed to high temperature environments.

[0008] An object of the present invention is to provide an optical laminate suitable for use in an image display device that may be exposed to a high temperature environment.

[0009] Solutions to the problem

[0010] The optical laminate generally contains residual monomers such as unreacted monomers remaining in the adhesive sheet. According to the research of the inventors, among the optical films that the optical laminate may contain, the phase difference film is susceptible to the influence brought by the residual monomers. Typically, the phase difference film is prone to cracks caused by repeated changes in ambient temperature. In addition, according to research, there is a tendency that the amount of residual monomers contained in the photocurable adhesive sheet is greater than that in the thermosetting adhesive sheet. This may be due to the fact that oxygen in the atmosphere is easy to hinder the curing of the photocurable composition near the surface of the sheet.

[0011] In view of the above, the present invention provides an optical laminate comprising:

[0012] Adhesive sheet formed from a photocurable composition containing a monomer group and / or a partial polymer of the monomer group, and

[0013] Retardation film,

[0014] The adhesive sheet is in contact with the retardation film directly or via a layer having a thickness of 10 μm or less.

[0015] The amount of residual monomers contained in the pressure-sensitive adhesive sheet is 16000 ppm (weight basis) or less.

[0016] In another aspect, the present invention provides an image display device including the optical layered body of the present invention.

[0017] Effects of the Invention

[0018] According to the present invention, it is possible to provide an optical laminated body that is suitable for use in an image display device that may be exposed to a high-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a cross-sectional view schematically showing an example of the optical layered body of the present invention.

[0020] Figure 2 This is a cross-sectional view schematically showing an example of the optical layered body of the present invention.

[0021] Figure 3 This is a cross-sectional view schematically showing an example of the optical layered body of the present invention.

[0022] Figure 4A This is a schematic diagram for explaining an example of a method for forming the pressure-sensitive adhesive sheet included in the optical layered body of the present invention.

[0023] Figure 4B This is a schematic diagram for explaining an example of a method for forming the pressure-sensitive adhesive sheet included in the optical layered body of the present invention.

[0024] Figure 4C This is a schematic diagram for explaining an example of a method for forming the pressure-sensitive adhesive sheet included in the optical layered body of the present invention. DETAILED DESCRIPTION

[0025] The optical layered body according to the first aspect of the present invention includes:

[0026] Adhesive sheet formed from a photocurable composition containing a monomer group and / or a partial polymer of the monomer group, and

[0027] Retardation film,

[0028] The adhesive sheet is in contact with the retardation film directly or via a layer having a thickness of 10 μm or less.

[0029] The amount of residual monomers contained in the pressure-sensitive adhesive sheet is 16000 ppm (weight basis) or less.

[0030] In the second aspect of the present invention, for example, the optical layered body of the first aspect includes the two pressure-sensitive adhesive sheets disposed so as to sandwich the retardation film.

[0031] In the third aspect of the present invention, for example, the optical layered body of the first or second aspect includes two or more of the pressure-sensitive adhesive sheets, and the total amount of the residual monomers contained in the two or more pressure-sensitive adhesive sheets is 16000 ppm (weight basis) or less.

[0032] In a fourth aspect of the present invention, for example, the optical layered body according to any one of the first to third aspects further includes a polarizing film.

[0033] In a fifth aspect of the present invention, for example, in the optical laminate of the fourth aspect, the polarizing film and the retardation film sandwich the pressure-sensitive adhesive sheet.

[0034] In a sixth aspect of the present invention, for example, in the optical layered body according to any one of the first to fifth aspects, the monomer group includes a (meth)acrylic monomer.

[0035] In a seventh aspect of the present invention, for example, in the optical layered body according to any one of the first to sixth aspects, the monomer group includes a carboxyl group-containing monomer.

[0036] In an eighth aspect of the present invention, for example, in the optical layered body of the seventh aspect, the content of the carboxyl group-containing monomer in the monomer group is 4.5% by weight or more.

[0037] In a ninth aspect of the present invention, for example, in the optical layered body according to any one of the first to eighth aspects, the monomer group includes a nitrogen atom-containing monomer.

[0038] In a tenth aspect of the present invention, for example, in the optical layered body according to any one of the first to ninth aspects,

[0039] The photocurable composition comprises a photopolymerization initiator.

[0040] The photopolymerization initiator is a compound having a chemical structure represented by the following formula (1) in the molecule:

[0041] [Chemical formula 1]

[0042]

[0043] R in the above formula (1) 1 and R 2Each independently is a C1-C8 alkyl group; the hydrogen atom is replaced by -OH, C1-C4 alkoxy, -CN, -COOR 51 、-OOCR 52 or -NR 53 R 54 Substituted C1-C4 alkyl; C3-C6 alkenyl; or -CH2-C6H4-R 55 ,

[0044] R 1 and R 2 They are optionally bonded to each other to form a C2-C9 alkylene group, a C3-C6 oxyalkylene group, or an azaalkylene group,

[0045] X is -OR 56 , or -NR 57 R 58 ,

[0046] R 51 is a C1-C8 alkyl group,

[0047] R 52 is a C1-C4 alkyl group,

[0048] R 53 and R 54 Each independently represents a hydrogen atom, a C1-C12 alkyl group; the hydrogen atom is selected from -OH, a C1-C4 alkoxy group, -CN and -COOR 59 At least one of the groups is substituted with a C2-C4 alkyl group; a C3-C5 alkenyl group; or a cyclohexyl group,

[0049] R 53 and R 54 may be mutually bonded and optionally substituted by -O- or -N(R 60 )-interrupted C3-C9 alkylene,

[0050] R 55 is a C1-C4 alkyl group,

[0051] R 56 is a hydrogen atom, -SiR 62 3. C1-C8 alkyl, or C3-C6 alkenyl,

[0052] R 57 and R 58 is a C1-C12 alkyl group; the hydrogen atom is selected from -OH, C1-C4 alkoxy, -CN and -COOR 63 A C2-C4 alkyl group; a C3-C5 alkenyl group; or a cyclohexyl group substituted with at least one group in

[0053] R 57 and R58 may be mutually bonded and optionally substituted by -O- or -N(R 64 )-interrupted C3-C9 alkylene,

[0054] R 59 is a C1-C4 alkyl group,

[0055] R 60 is a hydrogen atom, a C1-C4 alkyl group, an allyl group, a C1-C4 hydroxyalkyl group, -CH2CH2-COOR 61 or -CH2CH2CN,

[0056] R 61 is a C1-C4 alkyl group,

[0057] R 62 is a C1-C6 alkyl group,

[0058] R 63 is a C1-C4 alkyl group,

[0059] R 64 is a hydrogen atom, a C1-C4 alkyl group, an allyl group, a C1-C4 hydroxyalkyl group, -CH2CH2-COOR 65 or -CH2CH2CN,

[0060] R 65 is a C1-C4 alkyl group,

[0061] The above chemical structure can be bonded to a hydrogen atom or a substituted structure of a hydrogen atom via the carbon atom represented by * in the above formula (1).

[0062] In the 11th aspect of the present invention, for example, in the optical laminate of any one of the 1st to 10th aspects, the photocurable composition contains a first photopolymerization initiator having a relatively small first reaction rate, and a second photopolymerization initiator having a relatively large second reaction rate, and the ratio of the second reaction rate to the first reaction rate, represented by the ratio of polymerization rates A evaluated by the following measurement method using only the respective photopolymerization initiators, is 1.1 or more,

[0063] [Measurement method]

[0064] A mixed solution of 99 parts by weight of n-butyl acrylate and 1 part by weight of 4-hydroxybutyl acrylate as monomers and 0.1 parts by weight of a photopolymerization initiator to be evaluated is irradiated with ultraviolet rays to prepare a monomer slurry in which the above monomers are partially polymerized. The above ultraviolet irradiation is carried out until the viscosity of the above mixed solution at 30°C reaches 20 Pa·s. Next, a coating layer with a thickness of 20 μm formed by the prepared monomer slurry is formed between a pair of polyethylene terephthalate (PET) sheets each having a thickness of 75 μm; next, the coating layer is irradiated with ultraviolet rays using an LED having a peak wavelength of 340 nm±10 nm as a light source from one side of the above PET sheet. The illuminance and irradiation time of the above irradiated ultraviolet rays are set to 4 mW / cm 2 The polymerization rate A is determined as the polymerization rate of the monomer measured for the coating layer after photocuring by irradiation with the ultraviolet rays.

[0065] In a twelfth aspect of the present invention, for example, in the optical layered body according to any one of the first to eleventh aspects, the pressure-sensitive adhesive sheet has a surface subjected to a surface modification treatment.

[0066] In a 13th aspect of the present invention, for example, in the optical layered body according to any one of the 1st to 12th aspects, the thickness of the pressure-sensitive adhesive sheet is 50 μm or less.

[0067] In a fourteenth aspect of the present invention, for example, in the optical layered body according to any one of the first to thirteenth aspects, the anchoring force of the pressure-sensitive adhesive sheet with respect to the retardation film is 13 N / 25 mm or more.

[0068] An image display device according to a fifteenth aspect of the present invention includes the optical layered body according to any one of the first to fourteenth aspects.

[0069] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented with arbitrary modifications within the scope not departing from the gist of the present invention.

[0070] [Optical laminate]

[0071] An example of the optical layered body of the present embodiment is shown in Figure 1 . Figure 1 The optical laminate 10 (10A) comprises an adhesive sheet 1 and a phase difference film 2. The adhesive sheet 1 is directly in contact with the phase difference film 2. However, the adhesive sheet 1 and the phase difference film 2 may be in contact with each other via a layer having a thickness of less than 10 μm, preferably less than 5 μm. The layer may be a single layer or a multilayer. Examples of the layer are a primer layer, an antistatic layer, a protective layer, a coating layer, and a hard coating layer. The optical laminate 10 may be used in the form of an optical film with an adhesive sheet.

[0072] (Adhesive Sheet)

[0073] Adhesive sheet 1 is formed by a photocurable composition containing a monomer group and / or a partial polymer of the above-mentioned monomer group. The photocurable composition is a composition that forms adhesive sheet 1 by irradiation of light. The amount of residual monomers contained in adhesive sheet 1 is less than 16000ppm. The amount of residual monomers can be less than 15000ppm, less than 12000ppm, less than 10000ppm, less than 9000ppm, less than 8000ppm, less than 7000ppm, less than 6000ppm, less than 5000ppm, less than 5000ppm, less than 4500ppm, less than 4000ppm, less than 3500ppm, less than 3000ppm, less than 2500ppm, less than 2000ppm, and further can be less than 1500ppm. The amount of residual monomers is a small amount of adhesive sheet 1, which is not easy to produce cracks of phase difference film 2 caused by changes in ambient temperature. In addition, when the amount of residual monomers is less than 16000ppm, it is also suitable for improving the anchoring force relative to the phase difference film 2. In particular, a small amount of adhesive sheet 1 of less than 3500ppm, less than 2500ppm, and less than 2000ppm can also be suitable for improving the anchoring force relative to the phase difference film 2. In the adhesive sheet 1 with improved anchoring force, there is a possibility that the cohesive force of the adhesive sheet 1 is improved due to the reduction in the amount of low molecular weight compounds contained in the adhesive sheet 1. The lower limit of the amount of residual monomers is not particularly limited, for example, it is more than 300ppm, it can be more than 500ppm, and further can be more than 750ppm. The adhesive sheet 1 with a lower limit of the amount of residual monomers within the above range is suitable for suppressing the degradation of the phase difference film 2 that may occur due to exposure to light and heat when the laminated body containing the phase difference film 2 is irradiated with light to form the adhesive sheet 1. In this specification, "ppm" is all weight basis.

[0074] The amount of residual monomers in the pressure-sensitive adhesive sheet 1 can be evaluated by gas chromatography (GC) analysis.

[0075] Another example of the optical layered body of the present embodiment is shown in Figure 2 . Figure 2The optical laminate 10 (10B) has two adhesive sheets 1 (1A, 1B) configured in a manner of clamping a phase difference film 2. The optical laminate 10B has an adhesive sheet 1A, a phase difference film 2 and an adhesive sheet 1B in sequence. The amount of residual monomers contained in the two adhesive sheets 1A and 1B, that is, when the optical laminate 10B has two or more adhesive sheets 1, the amount of residual monomers contained in the two or more adhesive sheets 1 can be 16000 ppm or less in total, or it can be 15000 ppm or less, 12000 ppm or less, 10000 ppm or less, less than 10000 ppm, 9000 ppm or less, 8000 ppm or less, 7500 ppm or less, 7000 ppm or less, 6000 ppm or less, 5000 ppm or less, 4000 ppm or less, 3500 ppm or less, and further can be 3000 ppm or less. The optical laminate 10 with a small amount of the above-mentioned total of the amount of residual monomers is not easy to produce cracks in the phase difference film 2 caused by changes in ambient temperature. In addition, when the total amount of the residual monomers is less than 16000ppm, it is also suitable for improving the anchoring force between the phase difference film 2 and the adhesive sheet 1, and a particularly small amount of less than 3500ppm, less than 2500ppm, and less than 2000ppm of the optical laminate 10B can also be suitable for improving the anchoring force between the phase difference film 2 and the adhesive sheet 1. The lower limit of the amount is, for example, more than 300ppm in total, and can be more than 500ppm, more than 600ppm, more than 750ppm, and further more than 1000ppm. The optical laminate 10B having a lower limit within the above range is suitable for suppressing the degradation of the phase difference film 2 that may occur due to exposure to light and heat when the laminate containing the phase difference film 2 is irradiated with light to form an adhesive sheet 1.

[0076] The amount of residual monomers contained in the adhesive sheet 1 varies depending on, for example, the composition of the photocurable composition used to form the adhesive sheet 1, the type and amount of a photopolymerization initiator that may be contained in the photocurable composition, the formation conditions and thickness of the adhesive sheet 1, and the type and presence of post-treatment of the adhesive sheet 1. An example of post-treatment is the surface modification treatment described later.

[0077] Another example of the optical layered body of the present embodiment is shown in Figure 3 . Figure 3The optical laminate 10 (10C) further comprises a polarizing film 3. The polarizing film 3 sandwiches the adhesive sheet 1 (1A) together with the phase difference film 2. The optical laminate 10C comprises a polarizing film 3, an adhesive sheet 1A and a phase difference film 2 in sequence. In addition, the optical laminate 10C comprises a polarizing film 3, an adhesive sheet 1A, a phase difference film 2 and an adhesive sheet 1B in sequence. However, the position of the polarizing film 3 in the optical laminate 10 is not limited to this example. The polarizing film 3 is directly in contact with the adhesive sheet 1A. However, the polarizing film 3 and the adhesive sheet 1A may also be in contact with each other via a layer having a thickness of less than 10 μm, preferably less than 5 μm. Examples of such layers are described above.

[0078] Polarizing film 3 has a tendency to have large dimensional changes due to heat among optical films. The dimensional changes of polarizing film 3 impart a force that promotes the generation of cracks to phase difference film 2 contained in the same optical laminate 10. Therefore, when the optical laminate 10 further includes polarizing film 3, the present invention is particularly advantageous.

[0079] <Photocurable composition>

[0080] The photocurable composition capable of forming the adhesive sheet 1 includes, for example, a monomer group containing a (meth)acrylic monomer and / or a partial polymer of the monomer group. The content of the (meth)acrylic component in the photocurable composition, i.e., the (meth)acrylic monomer and its partial polymer, can be 50% by weight or more, 60% by weight or more, 70% by weight or more, and further can be 80% by weight or more. In this case, an acrylic adhesive sheet having a (meth)acrylic polymer and its cross-linked product as the main component can be formed. However, the photocurable composition is not limited to the above examples. In this specification, (meth)acrylic acid refers to acrylic acid and methacrylic acid. (Meth)acrylate refers to acrylate and methacrylate.

[0081] Examples of (meth)acrylic monomers include (meth)acrylic acid alkyl esters having an alkyl group having 1 to 20 carbon atoms in a side chain. The number of carbon atoms in the alkyl group may be 7 or less, 6 or less, 5 or less, or 4 or less. The alkyl group may be linear or branched. Examples of the alkyl (meth)acrylates are methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, and octadecyl (meth)acrylate. The alkyl (meth)acrylate may be n-butyl (meth)acrylate.

[0082] The content of the alkyl (meth)acrylate in the monomer group may be, for example, 40% by weight or more, 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or even 95% by weight or more. It should be noted that when calculating the content, the weight of the partial polymer is converted into the weight of each monomer before polymerization.

[0083] The monomer group may include a carboxyl-containing monomer. The carboxyl-containing monomer may be a (meth) acrylic monomer, in other words, the (meth) acrylic monomer may include a carboxyl-containing monomer. Examples of carboxyl-containing monomers are (meth) acrylic acid, (meth) carboxylethyl acrylate, (meth) carboxylpentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. The content of the carboxyl-containing monomer in the monomer group is, for example, 0.1 to 15% by weight. The lower limit of the content may be 0.5% by weight or more, 1% by weight or more, 2.5% by weight or more, 4.5% by weight or more, 5% by weight or more, 7.5% by weight or more, and further may be 9.5% by weight or more. The upper limit of the content may be 13% by weight or less, 11% by weight or less, 10% by weight or less, 9.5% by weight or less, and further may be 7.5% by weight or less. The use of a monomer group including a carboxyl-containing monomer is particularly suitable for reducing the amount of residual monomers in the adhesive sheet 1. The monomer group may also not include a carboxyl-containing monomer.

[0084] The monomer group may include a hydroxyl-containing monomer. The hydroxyl-containing monomer may be a (meth) acrylic monomer, in other words, the (meth) acrylic monomer may include a hydroxyl-containing monomer. The hydroxyl-containing monomer can contribute to the improvement of the cohesive force of the adhesive sheet. Examples of hydroxyl-containing monomers are 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, 6-hydroxyhexyl (meth) acrylate, 8-hydroxyoctyl (meth) acrylate, 10-hydroxydecyl (meth) acrylate, 12-hydroxylauryl (meth) acrylate, and methyl acrylate (4-hydroxymethylcyclohexyl). The hydroxyl-containing monomer is preferably 2-hydroxyethyl (meth) acrylate and 4-hydroxybutyl (meth) acrylate. The content of the hydroxyl-containing monomer in the monomer group is, for example, less than 5% by weight, less than 4% by weight, less than 3% by weight, less than 2% by weight, and further less than 1% by weight. The lower limit of the content is, for example, more than 0.01% by weight, more than 0.05% by weight, and further more than 0.1% by weight. The monomer group may not contain a hydroxyl group-containing monomer.

[0085] The monomer group may include nitrogen-containing monomers. According to the research of the present inventors, nitrogen-containing monomers can contribute to the reduction of the amount of residual monomers. Nitrogen-containing monomers refer to monomers having at least one nitrogen atom in the molecule (in one molecule). It should be noted that in this specification, monomers having a hydroxyl group and a nitrogen atom in the molecule are classified as nitrogen-containing monomers. Monomers having a carboxyl group and a nitrogen atom in the molecule are classified as carboxyl-containing monomers.

[0086] Preferred nitrogen atom-containing monomers include N-vinyl cyclic amide, (meth)acrylamide, etc. The nitrogen atom-containing monomers may be used alone or in combination of two or more.

[0087] The N-vinyl cyclic amide is preferably represented by the following formula (A).

[0088] [Chemical formula 2]

[0089]

[0090] In formula (A), R 1 is a divalent organic group, preferably a divalent saturated hydrocarbon group or an unsaturated hydrocarbon group, and more preferably a divalent saturated hydrocarbon group (for example, an alkylene group having 3 to 5 carbon atoms). 1 A ring structure is formed by direct bonding via a single bond.

[0091] As the N-vinyl cyclic amide represented by formula (A), N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidone, N-vinyl-2-caprolactam, N-vinyl-3-morpholinone, N-vinyl-1,3- More preferred are N-vinyl-2-pyrrolidone and N-vinyl-2-caprolactam, and even more preferred is N-vinyl-2-pyrrolidone.

[0092] Examples of (meth)acrylamide include (meth)acrylamide, N-alkyl (meth)acrylamide, and N,N-dialkyl (meth)acrylamide. Examples of N-alkyl (meth)acrylamide include N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-n-butyl (meth)acrylamide, and N-octylacrylamide. N-alkyl (meth)acrylamide also includes (meth)acrylamide having an amino group such as dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, and dimethylaminopropyl (meth)acrylamide.

[0093] Examples of the N,N-dialkyl(meth)acrylamide include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di-n-butyl(meth)acrylamide, and N,N-di-tert-butyl(meth)acrylamide.

[0094] (Meth)acrylamide also includes, for example, various N-hydroxyalkyl (meth)acrylamide. Examples of N-hydroxyalkyl (meth)acrylamide include N-methylol (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, N-(4-hydroxybutyl) (meth)acrylamide, and N-methyl-N-2-hydroxyethyl (meth)acrylamide.

[0095] (Meth)acrylamide also includes, for example, various N-alkoxyalkyl (meth)acrylamide. Examples of N-alkoxyalkyl (meth)acrylamide include N-methoxymethyl (meth)acrylamide and N-butoxymethyl (meth)acrylamide.

[0096] Examples of nitrogen atom-containing monomers other than N-vinyl cyclic amide and (meth)acrylamide include amino group-containing monomers such as aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinyl Azoles, vinyl isocyanates Heterocyclic monomers such as oxazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, N-methylvinylpyrrolidone, etc.; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide Itaconimide monomers such as itaconimide, N-2-ethylhexyl itaconimide, N-lauryl itaconimide, and N-cyclohexyl itaconimide; succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide; and acylimide group-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate.

[0097] The content of the nitrogen atom-containing monomer in the monomer group is, for example, 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, 18% by weight or less, 15% by weight or less, 14% by weight or less, 13% by weight or less, 12% by weight or less, 11% by weight or less, and further, 10% by weight or less. The lower limit of the content is, for example, 1% by weight or more, 2% by weight or more, 3% by weight or more, 4% by weight or more, 5% by weight or more, 6% by weight or more, 7% by weight or more, 8% by weight or more, 9% by weight or more, and further, 10% by weight or more.

[0098] The monomer group may include both a carboxyl group-containing monomer and a nitrogen atom-containing monomer.

[0099] In the photocurable composition, each of the above monomers may be included in the form of a partial polymer. The partial polymer may be any polymer of a homopolymer and a copolymer. The partial polymer may contribute to the stable formation of the coating layer described later by appropriately increasing the viscosity of the photocurable composition.

[0100] The photocurable composition generally contains a photopolymerization initiator. Examples of the photopolymerization initiator include a photoradical generator that generates radicals by visible light and / or ultraviolet light having a wavelength shorter than 450 nm.

[0101] Examples of photopolymerization initiators include benzoin ethers such as benzoin methyl ether, benzoin isopropyl ether, and benzoin dimethyl ether; substituted benzoin ethers such as anisole methyl ether; substituted acetophenones such as 2,2-diethoxyacetophenone and 2,2-dimethoxy-2-phenylacetophenone; α-hydroxyalkyl phenones such as 1-hydroxycyclohexyl phenyl ketone; substituted α-ol ketones such as 2-methyl-2-hydroxypropiophenone; aromatic sulfonyl chlorides such as 2-naphthalenesulfonyl chloride; photoactive oximes such as 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime; benzophenone, benzoylbenzoic acid, benzoylbenzoic acid, Benzophenone compounds such as methyl benzoate, 4-phenylbenzophenone, hydroxybenzophenone, acryloyl benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, 2,4-diethylthioxanthone; 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6 -bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-piperonyl-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis(trichloromethyl)-6-phenylvinyl-s-triazine, 2-(naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxy-naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-trichloromethyl-(piperonyl)-6-triazine, 2,4-trichloromethyl-(4'-methoxyphenylvinyl)-6-triazine, etc. Oxime ester compounds such as 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], O-(acetyl)-N-(1-phenyl-2-oxo-2-(4'-methoxy-naphthyl)ethylidene)hydroxylamine; phosphine compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; quinone compounds such as 9,10-phenanthrenequinone, camphorquinone, and ethylanthraquinone; borate ester compounds; carbazole compounds; imidazole compounds; and titanocene compounds. The photocurable composition may contain one or more photopolymerization initiators.

[0102] Another example of the photopolymerization initiator is a compound having a chemical structure represented by the following formula (1) (hereinafter referred to as chemical structure X) in the molecule. According to the study by the present inventors, this compound can contribute to the reduction of the amount of residual monomers.

[0103] [Chemical formula 3]

[0104]

[0105] R in the above formula (1) 1 and R 2 Each independently is a C1-C8 alkyl group; the hydrogen atom is replaced by -OH, C1-C4 alkoxy, -CN, -COOR 51 、-OOCR 52 or -NR 53 R 54 Substituted C1-C4 alkyl; C3-C6 alkenyl; or -CH2-C6H4-R 55 . R 1 and R 2 They may be bonded to each other to form a C2-C9 alkylene group, a C3-C6 oxyalkylene group, or an azaalkylene group. 51 is a C1-C8 alkyl group. 52 is a C1-C4 alkyl group. 53 and R 54 Each independently represents a hydrogen atom, a C1-C12 alkyl group; the hydrogen atom is selected from -OH, a C1-C4 alkoxy group, -CN and -COOR 59 A C2-C4 alkyl group; a C3-C5 alkenyl group; or a cyclohexyl group substituted with at least one group in R 53 and R 54 may be mutually bonded and optionally substituted by -O- or -N(R 60 )-interrupted C3-C9 alkylene. 55 is a C1-C4 alkyl group. 59 is a C1-C4 alkyl group. 60 is a hydrogen atom, a C1-C4 alkyl group, an allyl group, a C1-C4 hydroxyalkyl group, -CH2CH2-COOR 61 Or -CH2CH2CN. 61 It is a C1~C4 alkyl group.

[0106] X is -OR 56 , or -NR 57 R 58 . R 56 is a hydrogen atom, -SiR 62 3. C1-C8 alkyl or C3-C6 alkenyl. 57 and R 58 is a C1-C12 alkyl group; the hydrogen atom is selected from -OH, C1-C4 alkoxy, -CN and -COOR 63 A C2-C4 alkyl group; a C3-C5 alkenyl group; or a cyclohexyl group substituted with at least one group in R57 and R 58 may be mutually bonded and optionally substituted by -O- or -N(R 64 )-interrupted C3-C9 alkylene. 62 is a C1-C6 alkyl group. 63 is a C1-C4 alkyl group. 64 is a hydrogen atom, a C1-C4 alkyl group, an allyl group, a C1-C4 hydroxyalkyl group, -CH2CH2-COOR 65 Or -CH2CH2CN. 65 It is a C1~C4 alkyl group.

[0107] The chemical structure X can be bonded to a hydrogen atom or a substituted structure of a hydrogen atom via the carbon atom represented by * in formula (1).

[0108] The alkyl, alkoxy, alkenyl, alkylene, oxyalkylene, azaalkylene and hydroxyalkyl described in the description of formula (1) may be either unbranched or branched. In addition, including the description of formula (1), the description of "Cn1 to Cn2" (n1 and n2 are natural numbers) in this specification means that the number of carbon atoms is within the range of n1 to n2.

[0109] R 1 and R 2 Each of them independently may be a C1 to C8 alkyl group or a C3 to C6 alkenyl group, or may be a C1 to C8 alkyl group. 1 and R 2 Each of R may independently be a C1-C4 alkyl group, a C1-C3 alkyl group, or a C1-C2 alkyl group. 1 and R 2 It may be methyl.

[0110] R 1 and R 2 Can be the same.

[0111] X can be -OR 56 . R 56 It may be a hydrogen atom or a C1 to C8 alkyl group, or may be a hydrogen atom. In other words, X may be -OH.

[0112] R 1 , R 2 and X may adopt the above-mentioned preferred examples in any combination.

[0113] The chemical structure X may be a structure represented by the following formula (2). In the chemical structure X of formula (2), in the case of a substitution structure in which a hydrogen atom is bonded to a carbon atom represented by *, the substitution structure is identical to -COCR in formula (2). 1 XR 2The group is in a para position relative to the benzene ring of the chemical structure X.

[0114] [Chemical formula 4]

[0115]

[0116] The photopolymerization initiator may be a compound having two or more chemical structures X in one molecule.

[0117] The photopolymerization initiator may be a compound represented by the following formula (3). The compound of formula (3) has two chemical structures X in one molecule. The two chemical structures X are respectively located at two ends of the molecule of the photopolymerization initiator. More specifically, the two chemical structures X are bonded to each other through -A- and via the carbon atom of the phenylene group represented by *.

[0118] [Chemical formula 5]

[0119]

[0120] R in formula (3) 1 ' and R 2 'mutually and independently of R 1 and R 2 The ground can be used as R 1 and R 2 Take the group. R 1 ' and / or R 2 'Can be used with R 1 and / or R 2 Same. 1 , R 2 , R 1 ' and R 2 'Can all be the same.

[0121] X' in formula (3) is a group that can be used as X independently of X in formula (1). X' and X may be the same.

[0122] A is -O-, -CYR 3 -, or -C(CH3)R 4 .

[0123] Y is a hydrogen atom, -Cl, -Br, -OR 71 、-NR 72 R 73 , or -SR 74 . R 3 is a hydrogen atom, a C1-C8 alkyl group, a C3-C6 alkenyl group, a benzyl group, -CH2-C6H4-R 75 , or phenyl. 4It is a C1-C6 alkyl group or an alkylene group, and the alkylene group is bonded to the carbon atom of the phenylene group of the compound of formula (3).

[0124] R 71 is a hydrogen atom, -Si(R 76 )3, C1-C12 alkyl, C2-C18 acyl, -CO-NH-R 77 , C2-C20 hydroxyalkyl, C2-C20 methoxyalkyl, 3-R 78 -2-hydroxypropyl, 3-[1,3,3,3-tetramethyl-1-[(trimethylsilyl)oxy]disiloxyl]propyl, 2,3-dihydroxypropyl, or a C2-C21 hydroxyalkyl group whose carbon chain is interrupted by 1 to 9 oxygen atoms, or a C3-C25 alkyl group. 72 and R 73 Each independently is a C1-C12 alkyl group; the hydrogen atom is selected from -OH, C1-C4 alkoxy, -CN and -COOR 79 At least one of the groups is substituted with a C2-C4 alkyl group; a C3-C5 alkenyl group; a cyclohexyl group; or a C7-C9 phenylalkyl group. 72 and R 73 may be mutually bonded and optionally substituted by -O- or -N(R 80 )-interrupted C3-C9 alkylene. 74 C1-C18 alkyl, hydroxyethyl, 2,3-dihydroxypropyl, cyclohexyl, benzyl, phenyl, C1-C12 alkylphenyl, -CH2-COOR 81 -CH2CH2-COOR 82 , or -CH(CH3)-COOR 83 . R 75 is a C1-C4 alkyl group. 76 is a C1-C6 alkyl group. 77 is a C1-C12 alkyl group. 78 is a C1-C18 alkoxy group. 79 is a C1-C4 alkyl group. 80 is a hydrogen atom, a C1-C4 alkyl group, an allyl group, a benzyl group, a C1-C4 hydroxyalkyl group, -CH2CH2-COOR 84 , or -CH2CH2CN. 81 , R 82 and R 83 Each is independently a C1-C18 alkyl group. 84 It is a C1~C4 alkyl group.

[0125] The alkyl group, alkenyl group, acyl group, hydroxyalkyl group, methoxyalkyl group, alkoxy group, and phenylalkyl group described in the explanation of formula (3) may be unbranched or branched in the alkyl part or alkylene group.

[0126] R in formula (3) 1 , R 2 , R 1 ' and R 2 The preferred example of ' is the same as R in the description of the above formula (1) 1 and R 2 The preferred examples of X' in formula (3) are the same as the preferred examples of X in the description of formula (1). A can be -CYR 3 -. Y can be a hydrogen atom. R 3 A may be -CYR 3 -, and Y and R 3 In other words, A can be -CH2-.

[0127] R in formula (3) 1 , R 2 , R 1 '、R 2 ', X, X', and A can be any combination of the above-mentioned preferred examples.

[0128] The photopolymerization initiator may be a compound represented by the following formula (4): The compound of formula (4) is one of the compounds of formula (3).

[0129] [Chemical formula 6]

[0130]

[0131] Specific examples of photopolymerization initiators are shown in the following formulas (5) to (9). The photopolymerization initiator can be a compound represented by at least one chemical formula selected from formulas (5) to (9), a compound represented by at least one chemical formula selected from formulas (5) to (8), a compound represented by at least one chemical formula selected from formulas (5) to (7), or a compound represented by formula (5). It should be noted that the compound of formula (8) is derived from a vinyl compound having a chemical structure X in the side chain. More specifically, it is an oligomer of the vinyl compound.

[0132] [Chemical formula 7]

[0133]

[0134] [Chemical formula 8]

[0135]

[0136] [Chemical formula 9]

[0137]

[0138] [Chemical formula 10]

[0139]

[0140] [Chemical formula 11]

[0141]

[0142] The photopolymerization initiators represented by formulas (5) to (9) are commercially available as Omnirad 127, Esacure KIP 160, Esacureone, Esacure KIP 150, and Omnirad 1173 (all manufactured by IGM Resins). The photopolymerization initiator may be at least one selected from these.

[0143] Specific examples of photopolymerization initiators include 1-hydroxycyclohexyl-phenyl ketone, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)2-methylpropane-1-one. Among them, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)2-methylpropane-1-one is preferred. The above-mentioned photopolymerization initiators are commercially available as Omnirad184, Omnirad819, and Omnirad127, respectively (all manufactured by IGM Resin).

[0144] The amount of the photopolymerization initiator in the photocurable composition is, for example, 20 parts by weight or less, 10 parts by weight or less, 5.0 parts by weight or less, 4.0 parts by weight or less, 3.0 parts by weight or less, 2.5 parts by weight or less, 2.0 parts by weight or less, 1.5 parts by weight or less, 1.0 parts by weight or less, 0.5 parts by weight or less, 0.3 parts by weight or less, 0.25 parts by weight or less, and further, 0.2 parts by weight or less. The lower limit of the amount of the photopolymerization initiator is, for example, 0.01 parts by weight or more, 0.03 parts by weight or more, 0.05 parts by weight or more, 0.08 parts by weight or more, 0.1 parts by weight or more, 0.13 parts by weight or more, 0.15 parts by weight or more, and further, 0.18 parts by weight or more, relative to 100 parts by weight of the monomer group and its partial polymer.

[0145] The photocurable composition may contain one or two or more photopolymerization initiators.

[0146] The photocurable composition may include a first photopolymerization initiator having a relatively small first reaction rate, and a second photopolymerization initiator having a relatively large second reaction rate. The reaction rate of each photopolymerization initiator can be determined based on the polymerization rate achieved when the monomer is polymerized using only the photopolymerization initiator. The ratio of the second reaction rate to the first reaction rate is represented by the ratio of the polymerization rate A evaluated by the following measurement method using only each photopolymerization initiator, which is 1.1 or more. The ratio of the polymerization rate A can be 1.15 or more, or 1.2 or more, 1.22 or more, 1.25 or more, and further 1.27 or more. The upper limit of the ratio is not particularly limited, for example, 3 or less. It should be noted that the ratio of the polymerization rate A is determined by [polymerization rate A when only the second photopolymerization initiator is used] / [polymerization rate A when only the first photopolymerization initiator is used].

[0147] [Measurement method]

[0148] A mixed solution of 99 parts by weight of n-butyl acrylate and 1 part by weight of 4-hydroxybutyl acrylate as monomers and 0.1 parts by weight of a photopolymerization initiator to be evaluated was irradiated with ultraviolet rays to prepare a monomer slurry in which the above monomers were partially polymerized. The ultraviolet irradiation was carried out until the viscosity of the mixed solution at 30°C reached 20 Pa·s. Next, a coating layer with a thickness of 20 μm formed by the prepared monomer slurry was formed between a pair of polyethylene terephthalate (PET) sheets each having a thickness of 75 μm. Next, the coating layer was irradiated with ultraviolet rays using an LED having a peak wavelength of 340 nm ± 10 nm as a light source from one side of the PET sheet. The irradiation intensity and irradiation time of the ultraviolet rays were set to 4 mW / cm 2 The polymerization rate of the above monomers measured on the coating layer after photocuring by irradiation with ultraviolet rays was determined as the polymerization rate A.

[0149] According to the research of the inventors, the combination of the first and second photopolymerization initiators affects the state of polymerization when forming the adhesive sheet, thereby contributing to the reduction of the amount of residual monomers. It should be noted that the composition of the monomer slurry used to evaluate the polymerization rate A is known as a general composition for forming acrylic adhesive sheets. In addition, the above-mentioned ultraviolet irradiation conditions are suitable for evaluating the state of polymerization.

[0150] The polymerization rate A of the first photopolymerization initiator may be 80% or less, 79% or less, or 78% or less. The lower limit of the polymerization rate A is, for example, 65% or more, 66%, 67%, 68%, 69%, or 70% or more.

[0151] The polymerization rate A of the second photopolymerization initiator may be 90% or more, 91% or more, 92% or more, 93% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more. The upper limit of the polymerization rate A is, for example, 99.9% or less, or 99.5% or less.

[0152] The polymerization rates A of the first photopolymerization initiator and the second photopolymerization initiator may both satisfy the above ranges. For example, the polymerization rate A of the first photopolymerization initiator may be 80% or less, and the polymerization rate A of the second photopolymerization initiator may be 90% or more.

[0153] Examples of the first and second photopolymerization initiators are benzoyl ethers, substituted benzoyl ether compounds, substituted acetophenone compounds, α-hydroxyacetophenone compounds, substituted α-ketoalcohol compounds, aromatic sulfonyl chloride compounds, photoactive oximes, benzophenone compounds, thioxanthone compounds, triazine compounds, oxime ester compounds, phosphine compounds, quinone compounds, borate ester compounds, carbazole compounds, imidazole compounds and titanocene compounds.

[0154] The first photopolymerization initiator is preferably an α-hydroxyacetophenone compound. The first photopolymerization initiator, which is an α-hydroxyacetophenone compound, is particularly suitable for increasing the molecular weight of the polymer in combination with the second photopolymerization initiator. The number of α-hydroxyacetophenone structures in one molecule of the first photopolymerization initiator is, for example, 1 to 3, preferably 1 or 2, and more preferably 1.

[0155] A specific example of the first photopolymerization initiator is 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylacetone. This photopolymerization initiator is an α-hydroxyacetophenone compound and is commercially available as Omnirad 2959 (manufactured by IGM Resins).

[0156] The second photopolymerization initiator is not limited and may be an α-hydroxyacetophenone compound. The second photopolymerization initiator, which is an α-hydroxyacetophenone compound, is particularly suitable for increasing the molecular weight of the polymer in combination with the first photopolymerization initiator, especially the first photopolymerization initiator, which is an α-hydroxyacetophenone compound. The number of α-hydroxyacetophenone structures in one molecule of the second photopolymerization initiator is, for example, 1 to 3, preferably 1 or 2, and more preferably 2.

[0157] Including a preferred embodiment, the second polymerization initiator may be the above-mentioned compound having a chemical structure X in the molecule.

[0158] The photocurable composition may contain one or two or more first photopolymerization initiators. The photocurable composition may contain one or two or more second photopolymerization initiators.

[0159] The weight ratio of the amount X1 of the first photopolymerization initiator to the amount X2 of the second photopolymerization initiator is, for example, 5:1 to 1:5, 4:1 to 1:4, 3:1 to 1:3, 2:1 to 1:2, or 1.5:1 to 1:1.5.

[0160] The photocurable composition may contain a crosslinking agent. An example of a crosslinking agent is a multifunctional monomer having two or more polymerizable functional groups in one molecule. The multifunctional monomer may be a (meth)acrylic monomer. An example of a multifunctional monomer is a monomer having two or more C=C bonds in one molecule, and a monomer having one or more C=C bonds and one or more epoxy groups, aziridine groups, The polyfunctional monomer preferably has two or more C═C bonds in one molecule.

[0161] Examples of the multifunctional monomer include: multifunctional acrylates (ester compounds formed by polyols and (meth)acrylic acid, etc.) such as (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol diacrylate (NDDA), 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate; allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. The polyfunctional monomer is preferably a polyfunctional acrylate, and more preferably trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, or dipentaerythritol hexa(meth)acrylate.

[0162] The amount of the crosslinking agent varies depending on the molecular weight, the number of functional groups, etc., and is, for example, 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, and further 0.5 parts by weight or less per 100 parts by weight of the total of the monomer group and its partial polymer. The lower limit of the amount of the crosslinking agent is, for example, 0.01 parts by weight or more, and further 0.05 parts by weight or more.

[0163] The photocurable composition may contain additives other than those mentioned above. Examples of the additives include chain transfer agents, silane coupling agents, viscosity modifiers, tackifiers, plasticizers, softeners, antioxidants, fillers, colorants, antioxidants, surfactants, antistatic agents, and ultraviolet absorbers.

[0164] The amount of the silane coupling agent is, for example, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.5 parts by weight or less, per 100 parts by weight of the total of the monomer group and its partial polymer. The lower limit of the amount is, for example, 0.1 parts by weight or more, or 0.2 parts by weight or more. The photocurable composition may not contain a silane coupling agent.

[0165] The content of the solvent in the photocurable composition is, for example, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, and further 0.5% by weight or less. The photocurable composition may contain substantially no solvent. Substantially containing no solvent means that a solvent from an additive or the like is allowed to be contained at a content of, for example, 0.1% by weight or less, preferably 0.05% by weight or less, and more preferably 0.01% by weight or less.

[0166] The viscosity of the photocurable composition is preferably 5 to 100 poise. A photocurable composition having a viscosity within the above range is particularly suitable for forming a coating layer described below.

[0167] The polymerization rate of the monomer group in the pressure-sensitive adhesive sheet 1 is preferably 95% or more. The polymerization rate may be 96% or more, 97% or more, 98% or more, or even 99% or more.

[0168] The gel fraction of the pressure-sensitive adhesive sheet 1 may be, for example, 50% or more, 75% or more, 80% or more, or even 85% or more.

[0169] The thickness of the adhesive sheet 1 is, for example, 70 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, 25 μm or less, or 20 μm or less. The lower limit of the thickness is, for example, 2 μm or more, 5 μm or more, or 10 μm or more.

[0170] The adhesive sheet 1 may have a surface 4 to which a surface modification treatment is applied (hereinafter, "modified surface") . Typically, the surface modification treatment is a treatment using active energy rays. The surface modification treatment may be, for example, at least one selected from corona treatment, plasma treatment, excimer UV light treatment, and flame treatment, and may be corona treatment and / or plasma treatment, or may be corona treatment. Each surface modification treatment may be implemented by a corresponding known treatment device.

[0171] The conditions of the surface modification treatment as the corona treatment are represented by the discharge amount, for example, 0.6 to 100 kJ / m 2 The lower limit of discharge can be 1kJ / m 2 Above, 2kJ / m 2 Above, 5kJ / m 2 Above, 7kJ / m 2 Above, 10kJ / m 2 Above, 13kJ / m 2 Above, 15kJ / m 2 Above, 20kJ / m 2 Above, 25kJ / m 2 Above, 30kJ / m 2 Above, it can be 35kJ / m 2 The upper limit of the discharge amount can be 70 kJ / m 2 Below, 60kJ / m 2 Below, 50kJ / m 2 Below, 45kJ / m 2 Below, 40kJ / m 2 Below, 30kJ / m 2 Below, 20kJ / m 2 Below, and further can be 18kJ / m 2 the following.

[0172] Figure 1 The adhesive sheet 1 has a modified surface 4 on the phase difference film 2 side. This method is particularly suitable for improving the anchoring force of the adhesive sheet 1 relative to the phase difference film 2. The adhesive sheet 1 may have a modified surface 4 on the side opposite to the phase difference film 2 side, or may have a modified surface 4 on both the phase difference film 2 side and the opposite side.

[0173] The anchoring force of the adhesive sheet 1 to the phase difference film 2 can be 10N / 25mm or more, 12N / 25mm or more, 13N / 25mm or more, 14N / 25mm or more, 15N / 25mm or more, 16N / 25mm or more, 17N / 25mm or more, and further can be 18N / 25mm or more. The upper limit of the anchoring force is, for example, 50N / 25mm or less, and can be 30N / 25mm or less.

[0174] Improving the anchoring force of the pressure-sensitive adhesive sheet 1 to the phase difference film 2 can, for example, contribute to suppressing the peeling between the pressure-sensitive adhesive sheet 1 and the phase difference film 2. The optical laminate with suppressed peeling is suitable for suppressing the degradation of image quality in image display devices that may be used in harsh environments for a long time.

[0175] The anchoring force of the adhesive sheet 1 relative to the phase difference film 2 can be measured by the following method. The laminate comprising the phase difference film 2 and the adhesive sheet 1 is cut into a width of 25mm×length of 150mm to make a test piece. Next, the entire surface of the phase difference film 2 possessed by the test piece is superimposed on the stainless steel test plate via a double-sided tape, and a 2kg roller is reciprocated once to press them together. Next, the adhesive sheet 1 possessed by the test piece is superimposed on the evaluation sheet, and a 2kg roller is reciprocated once to press them together. The evaluation sheet has a size of 30mm in width×150mm in length, and is not particularly limited as long as it does not peel off from the adhesive sheet 1 during the test. As an evaluation sheet, for example, an ITO film (125Tetoraito OES (manufactured by Oike Industry Co., Ltd.) etc.) can be used. Next, using a commercially available tensile testing machine, the adhesive sheet 1 was peeled off from the phase difference film 2 at a peeling angle of 180° and a tensile speed of 300 mm / min while holding the evaluation sheet, and the average value of the peeling force at this time was determined as the anchoring force of the adhesive sheet 1 to the phase difference film 2. The above test was performed in an atmosphere of 23°C±5°C.

[0176] (Phase difference film)

[0177] A film obtained by stretching a polymer film or a film obtained by orienting and fixing a liquid crystal material can be used as the retardation film 2. The retardation film 2 has birefringence in the plane and / or in the thickness direction, for example.

[0178] The phase difference film 2 includes a phase difference film for antireflection (refer to Japanese Patent Application Publication No. 2012-133303

[0221] ,

[0222] , and

[0228] ), a phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303

[0225] and

[0226] ), and a tilted orientation phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303

[0227] ).

[0179] The specific structure of the retardation film 2, such as the retardation value, the arrangement angle, the three-dimensional birefringence, whether it is a single layer or a multilayer, etc., is not particularly limited, and a known retardation film can be used.

[0180] The thickness of the retardation film 2 is, for example, 30 to 200 μm, or preferably 40 to 150 μm.

[0181] The retardation film 2 may include, for example, a quarter-wave plate and / or a half-wave plate in which a liquid crystal material is oriented and fixed.

[0182] The phase difference film 2 containing a cycloolefin polymer is particularly prone to cracking. In addition, for the phase difference film 2 as a stretched film, cracking is more likely to occur in the case of a uniaxially stretched film than in the case of a biaxially stretched film. Therefore, the present invention is particularly advantageous in the case of the phase difference film 2 containing a cycloolefin polymer and in the case of a uniaxially stretched film.

[0183] The retardation film 2 may have a modification-treated surface. Figure 1 The phase difference film 2 has a modified surface 5 on one side of the adhesive sheet 1. This embodiment is particularly suitable for improving the anchoring force between the phase difference film 2 and the adhesive sheet 1. Examples of the surface modification treatment including preferred examples are as described above.

[0184] An example of a residual monomer that may be contained in the retardation film 2 and the optical laminate 10 is a (meth)acrylic monomer. Examples of the (meth)acrylic monomer are the same as those of the (meth)acrylic monomer contained in the photocurable composition that can form the adhesive sheet 1 .

[0185] (Polarizing Film)

[0186] The polarizing film 3 includes a polarizer. Typically, the polarizing film 3 includes a polarizer and a protective film (transparent protective film). The protective film is, for example, arranged in contact with the main surface (surface with the widest area) of the polarizer. The polarizer can be arranged between two protective films. The protective film can be arranged on at least one side of the polarizer.

[0187] The polarizer is not particularly limited, and examples thereof include: a polarizer obtained by adsorbing a dichroic substance such as iodine and a dichroic dye on a hydrophilic polymer film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, and a partially saponified film of an ethylene-vinyl acetate copolymer, and then uniaxially stretching the film; a polyene oriented film such as a dehydrated product of polyvinyl alcohol and a dehydrochlorinated product of polyvinyl chloride, etc. Typically, the polarizer is formed of a polyvinyl alcohol film (polyvinyl alcohol films include partially saponified films of ethylene-vinyl acetate copolymers) and a dichroic substance such as iodine.

[0188] The thickness of the polarizer is not particularly limited, for example, it is 80 μm or less, and can be 50 μm or less, 30 μm or less, 28 μm or less, 25 μm or less, 20 μm or less, and further can be 18 μm or less. The lower limit of the thickness of the polarizer is not particularly limited, for example, it is 1 μm or more, and can be 5 μm or more, 10 μm or more, and further can be 15 μm or more. The dimensional change caused by heat in a thin polarizer (for example, with a thickness of 20 μm or less) is suppressed, which can contribute to the improvement of the durability of the optical laminate, especially the durability at high temperatures. In addition, since there is a tendency that the greater the thickness of the polarizer, the greater the dimensional change caused by heat, the present invention is particularly advantageous, for example, when the thickness of the polarizer exceeds 20 μm, especially when it is 25 μm or more.

[0189] As the material of the protective film, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier, isotropy, etc. can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the protective film can be a thermosetting resin or ultraviolet curing resin such as (meth)acrylic acid, urethane, acrylic urethane, epoxy, silicone, etc. In the case where the polarizing film has two protective films, the materials of the two protective films can be the same or different from each other. For example, a protective film formed of a thermoplastic resin can be bonded to one main surface of the polarizer via an adhesive, and a protective film formed of a thermosetting resin or an ultraviolet curing resin can be bonded to the other main surface of the polarizer. The protective film can contain one or more arbitrary additives. Examples of the additive include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.

[0190] The thickness of the protective film can be appropriately determined, and is generally, for example, 5 to 200 μm, preferably 10 to 80 μm, from the viewpoints of strength, workability such as handling properties, and thin film properties.

[0191] The polarizer and the protective film are usually bonded together via a water-based adhesive or the like. Examples of the water-based adhesive include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latex, water-based polyurethane, and water-based polyester. Other adhesives other than the above-mentioned adhesives include ultraviolet curing adhesives and electron beam curing adhesives. Electron beam curing polarizer adhesives show suitable adhesion to various protective films. The adhesive may also contain a metal compound filler.

[0192] The protective film may be provided with a hard coating layer on the surface opposite to the surface bonded to the polarizer, and may be subjected to treatment for the purpose of anti-reflection, anti-blocking, diffusion, anti-glare, etc.

[0193] The polarizing film 3 may be a circular polarizing film.

[0194] The thickness of the polarizing film 3 is, for example, 500 μm or less, 300 μm or less, 200 μm or less, 100 μm or less, or 60 μm or less. The lower limit of the thickness is, for example, 10 μm or more, 25 μm or more, or 40 μm or more.

[0195] The optical laminate 10 may also include layers other than the adhesive sheet 1, the phase difference film 2, and the polarizing film 3. Examples of such layers include optical films other than the phase difference film 2 and the polarizing film 3, primer layers, antistatic layers, protective layers, coating layers, hard coating layers, glass covers, adhesive sheets other than the adhesive sheet 1, and substrate sheets that can be used for forming the adhesive sheet 1.

[0196] [Method for producing optical layered body]

[0197] The optical laminate 10 can be formed, for example, by laminating an adhesive sheet 1, a phase difference film 2, and other layers such as a polarizing film 3 used as needed. The adhesive sheet 1 can be formed, for example, by irradiating a first laminate 15 including a substrate sheet 21, a coating layer 22 containing a photocurable composition, and a release liner 23 in this order with light 14 (see Figure 4A to Figure 4C ). The coating layer 22 is irradiated with the light 14 and cured to form the adhesive sheet 1.

[0198] exist Figure 4A In the example, the light 14 is irradiated from one side of the substrate sheet 21. At this time, the light 14 passes through the substrate sheet 21 and reaches the coating layer 22. However, the light 14 may be irradiated from one side of the release liner 23, or from both sides of the release liner 23 and the substrate sheet 21 ( Figure 4B The formed pressure-sensitive adhesive sheet 1 is sandwiched between the base sheet 21 and the release liner 23 to constitute a part of the second laminate 16 until the release liner 23 is peeled off.

[0199] An example of the base material of the release liner 23 (hereinafter referred to as "base material") is a resin film. Examples of the resin that can be contained in the base material are polyesters such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyether sulfone, polycarbonate, polyamide, polyimide, polyolefin, (meth) acrylic resin, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl alcohol, polyarylate, and polyphenylene sulfide. The resin is preferably a polyester such as polyethylene terephthalate.

[0200] The release liner 23 may have the transmittance of the light 14 or may have the same degree of transmittance of the light 14 as the base sheet 21 .

[0201] The thickness of the release liner 23 is, for example, 10 to 200 μm, or 25 to 150 μm.

[0202] The release liner 23 may include a layer other than the lining substrate. The release liner 23 may include a release layer. The release liner 23 may include, for example, a lining substrate and a release layer formed on one side of the lining substrate. The release liner 23 may be used in a manner such that the release layer is on the coating layer 22 side.

[0203] Typically, the release layer is a cured layer of a release agent composition containing a release agent. The release agent can use various release agents such as silicone release agents, fluorine release agents, long-chain alkyl release agents, fatty acid amide release agents, and silica powder. The release liner 23 can have a cured layer of a release agent composition containing a silicone release agent as a main component (hereinafter, "silicone release layer"). The silicone release layer is particularly suitable for balancing the adhesion and releasability relative to the adhesive sheet 1. It should be noted that in this specification, the main component refers to the component with the largest content.

[0204] The silicone release agent includes various curable silicone materials such as addition reaction type, condensation reaction type, ultraviolet curing type, electron beam curing type, solvent-free type, etc., preferably addition reaction curing type silicone materials. Addition reaction curing type silicone materials are particularly suitable for forming a release layer that takes into account both adhesion and peelability with respect to the adhesive sheet 1. The curable silicone material can be a silicone modified resin obtained by introducing reactive silicone into an organic resin such as urethane, epoxy, alkyd resin, etc. by graft polymerization.

[0205] Examples of addition reaction curing silicone materials are polyorganosiloxanes having vinyl or alkenyl groups in the molecule. Addition reaction curing silicone materials may not have hydrosilyl groups. Examples of alkenyl groups are 3-butenyl, 4-pentenyl, 5-hexenyl, 6-heptenyl, 7-octenyl, 8-nonenyl, 9-decenyl, 10-undecenyl and 11-dodecenyl. Examples of polyorganosiloxanes are copolymers of polyalkylalkylsiloxanes such as polydimethylsiloxane, polydiethylsiloxane and polymethylethylsiloxane, polyalkylarylsiloxane, and poly(dimethylsiloxane-diethylsiloxane) and other monomers containing Si atoms. Polyorganosiloxane is preferably polydimethylsiloxane.

[0206] A mold release composition containing a silicone-based mold release agent as a main component (hereinafter, "silicone mold release composition") generally contains a crosslinking agent. An example of the crosslinking agent is a polyorganosiloxane having a hydrosilyl group. The crosslinking agent may have two or more hydrosilyl groups in one molecule.

[0207] The silicone release agent composition may also contain a curing catalyst. Examples of the curing catalyst are platinum catalysts. Examples of platinum catalysts are chloroplatinic acid, olefin complexes of platinum, and olefin complexes of chloroplatinic acid. The amount of the platinum catalyst used is, for example, 10 to 1000 ppm (weight basis, converted to platinum) relative to the total solid content of the composition.

[0208] The silicone release agent composition may also contain additives. Examples of additives are release control agents and adhesion improvers. Examples of release control agents are unreactive silicone resins, and more specifically, organosiloxanes such as octamethylcyclotetrasiloxane and MQ resins. The total amount of release control agents and adhesion improvers is, for example, 1 to 30% by weight relative to the total solid content of the composition. Other examples of additives are fillers, antistatic agents, antioxidants, ultraviolet absorbers, plasticizers, and colorants. The total amount of other additives is, for example, 10% by weight or less relative to the total solid content of the composition.

[0209] The silicone release agent composition may also contain an organic solvent. Examples of organic solvents are hydrocarbon solvents such as cyclohexane, n-hexane, and n-heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, and butanol. Two or more organic solvents may also be contained. The amount of organic solvent used is preferably 80 to 99.9% by weight of the silicone release agent composition.

[0210] The release layer can be formed, for example, by heating and drying a coating film containing a release agent composition formed on a lining substrate. The release agent composition can be applied by various coating methods such as roller coating, roller lick coating, gravure coating, reverse coating, roller brush, spray coating, dip roller coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating. Heating and drying can be performed by hot air drying, for example. The heating temperature and time vary depending on the heat resistance of the lining substrate, and are generally 80 to 150° C. and about 10 seconds to 10 minutes. As required, irradiation with active energy rays such as ultraviolet rays can also be used in combination.

[0211] The thickness of the release layer is, for example, 10 to 300 nm. The upper limit of the thickness may be 200 nm or less, 150 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, less than 100 nm, 90 nm or less, 80 nm or less, 70 nm or less, less than 70 nm, and further may be 65 nm or less. The lower limit of the thickness may be 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, 40 nm or more, 45 nm or more, and further may be 50 nm or more.

[0212] The release liner 23 may be in the form of a single sheet or in the form of a long strip.

[0213] An example of the base sheet 21 is a resin film. Examples of the resin contained in the base sheet 21 are the same as examples of the resin that can be contained in the backing base.

[0214] It is preferred that the base sheet 21 has excellent transmittance to the light 14 .

[0215] The thickness of the base sheet 21 is, for example, 10 to 200 μm, or 25 to 150 μm.

[0216] The substrate sheet 21 may have a release layer on the surface of the coating layer 22 side. The examples of the release layer and its preparation method that the substrate sheet 21 may have are the same as the examples of the release layer and its preparation method that the release liner 23 may have. It is also possible to have a release layer on both the release liner 23 and the substrate sheet 21. In this case, the release layers of the two may be formed by a release agent composition containing the same release agent as a main component. In addition, the thickness of the release layers of the two may be different, for example, the release layer of the substrate sheet 21 may be thicker.

[0217] The base sheet 21 can generally be selected to have a greater release force with the pressure-sensitive adhesive sheet 1 than the release liner 23 .

[0218] The base sheet 21 may be in a single sheet shape or in a long strip shape.

[0219] The first laminate 15 can be formed, for example, by forming a coating layer 22 on a substrate sheet 21 (or a release liner 23), and disposing a release liner 23 (or a substrate sheet 21) on the formed coating layer 22. Alternatively, the first laminate 15 can be formed by coating the photocurable composition so as to flow into a space between the substrate sheet 21 and the release liner 23, which are maintained at a predetermined interval so that their main surfaces face each other.

[0220] The coating layer 22 can be formed by various coating methods such as roll coating, lick roll coating, gravure coating, reverse coating, roller brushing, spray coating, dip roll coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating.

[0221] The thickness of the coating layer 22 can be adjusted according to the target thickness of the adhesive sheet 1 .

[0222] The light 14 irradiated to the first stack 15 is, for example, visible light or ultraviolet light having a wavelength shorter than 450 nm. The light 14 may include light of a wavelength in the same region as the absorption wavelength of the photopolymerization initiator contained in the photocurable composition. The light 14 obtained by cutting off short-wavelength light having a wavelength of less than 300 nm through an optical filter or the like may be irradiated, and cutting off the short-wavelength light is suitable for suppressing the degradation of the substrate sheet 21 and / or the release liner 23 caused by the light 14. The light source of the light 14 is, for example, an irradiation device having an ultraviolet irradiation lamp. Examples of ultraviolet irradiation lamps are ultraviolet LEDs, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultrahigh-pressure mercury lamps, metal halide lamps, xenon lamps, microwave-excited mercury lamps, black light lamps, chemical lamps, sterilization lamps, low-pressure discharge mercury lamps, and excimer lasers. Two or more ultraviolet irradiation lamps may also be combined.

[0223] The irradiation of the light 14 may be continuous or intermittent.

[0224] The irradiation intensity of the light 14 is, for example, 1 to 20 mW / cm 2 The irradiation time of the light 14 is, for example, 5 minutes to 5 hours. The cumulative light intensity of the light 14 on the first stack 15 is, for example, 100 to 5000 mJ / cm 2 .

[0225] Next, the release liner 23 is peeled off from the second laminate 16 to expose the surface of the adhesive sheet 1. The retardation film 2 is disposed on the exposed surface of the adhesive sheet 1 to form the optical laminate 10. The exposed surface of the adhesive sheet 1 may be subjected to a surface modification treatment before the retardation film 2 is disposed.

[0226] The optical layered body of the present embodiment can be distributed and stored in the form of a roll body in which a belt-shaped optical layered body is rolled up, or in the form of a single sheet-shaped optical layered body.

[0227] Typically, the optical laminate of the present embodiment can be used in an image display device. The image display device can be formed by, for example, bonding the optical laminate 10 to an image display panel. The bonding is performed, for example, by an adhesive sheet 1. The image display device can be an organic EL display or a liquid crystal display. However, the image display device is not limited to the above examples. The image display device can also be a field luminescence (EL) display, a plasma display (PD), a field emission display (FED: Field Emission Display), etc. The image display device can be an image display device for use that may be exposed to a high temperature environment, and typically, it can be a vehicle-mounted image display device. However, the use of the image display device is not limited. The image display device can be used for various purposes such as home appliances and public information displays (PID).

[0228] Example

[0229] Hereinafter, the present invention will be described in more detail by way of examples. However, the present invention is not limited to the examples shown below.

[0230] [Preparation of polarizing film]

[0231] (Polarizing film A)

[0232] Between rollers with different speed ratios, a polyvinyl alcohol film with a thickness of 80 μm was dyed in an iodine solution with a temperature of 30°C and a concentration of 0.3% for 1 minute and stretched to 3 times. Next, it was immersed in an aqueous solution at a temperature of 60°C containing boric acid at a concentration of 4% and potassium iodide at a concentration of 10% for 0.5 minutes and stretched to a total stretch ratio of 6 times. Next, it was immersed in an aqueous solution at a temperature of 30°C containing potassium iodide at a concentration of 1.5% for 10 seconds and washed, and then dried at 50°C for 4 minutes, thereby obtaining a polarizer with a thickness of 18 μm. A transparent protective film with a thickness of 30 μm formed of a modified acrylic polymer having a lactone ring structure was bonded to one side of the polarizer via a polyvinyl alcohol adhesive. Furthermore, a transparent protective film with a thickness of 47 μm formed with a hard coating (HC) on a cellulose triacetate film (manufactured by Konica Minolta, trade name "KC4UY") was bonded to the other side of the polarizer via a polyvinyl alcohol adhesive. The film was dried by heating in an oven set at 70° C. for 5 minutes to prepare a polarizing film A. Furthermore, the film was discharged at a discharge amount of 63 W / (m 2 (a) The surface of the polarizing film A on the transparent protective film side formed of a modified acrylic polymer was subjected to a corona treatment.

[0233] (Polarizing film B)

[0234] The stretching conditions were changed, and a polarizer with a thickness of 28 μm was obtained in the same manner as the preparation of polarizing film A, except for this. A transparent protective film with a thickness of 30 μm formed from a modified acrylic polymer having a lactone ring structure was adhered to one side of the polarizer using a polyvinyl alcohol-based adhesive. Furthermore, a transparent protective film with a thickness of 40 μm formed on a cellulose triacetate film (manufactured by Konica Minolta, trade name "KC4UY") with a hard coating layer (HC) was adhered to the other side of the polarizer using a polyvinyl alcohol-based adhesive. The film was heated and dried in an oven set at 70°C for 5 minutes, thereby preparing polarizing film B. Furthermore, the film was heated and dried in an oven set at 70°C for 5 minutes, and the discharge amount was 63 W / (m 2 (a) The surface of the polarizing film B on the transparent protective film side formed of a modified acrylic polymer was subjected to a corona treatment.

[0235] [Preparation of retardation film]

[0236] A biaxially oriented polypropylene film (Toray, trade name "TORAYFAN" BO 2570A-5, thickness 60 μm) was bonded to both sides of a polymer film (Zeonor Co., Ltd., trade name "Zeonor ZF14-100", thickness 100 μm) containing a resin obtained by hydrogenating a ring-opening polymer of a norbornene-based monomer via an acrylic adhesive layer (thickness 15 μm). Then, the film was stretched to 1.38 times in an air circulation constant temperature oven at 146°C±1°C in the longitudinal direction by a roll stretching machine to produce a retardation film with a thickness of 108 μm.

[0237] [Preparation of monomer slurry]

[0238] (Synthesis example 1)

[0239] 99 parts by weight of n-butyl acrylate (BA), 1 part by weight of 4-hydroxybutyl acrylate (HBA), 10 parts by weight of acrylic acid (AA), and 0.1 parts by weight of Omnirad184 (1-hydroxycyclohexyl-phenyl ketone, manufactured by IGM RESINS) as a photopolymerization initiator were placed in a four-necked flask and irradiated with ultraviolet rays in a nitrogen atmosphere to obtain a partially photopolymerized monomer syrup A1. The ultraviolet rays were irradiated until the viscosity of the liquid in the flask (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached about 20 Pa·s.

[0240] (Synthesis example 2)

[0241] Except that the monomers used were changed as shown in Table 1, monomer slurries A2 to A14 were prepared in the same manner as in the monomer slurry A1.

[0242] [Table 1]

[0243]

[0244] The abbreviations in Table 1 are as follows. It should be noted that Omnirad2959 and Omnirad127 are α-hydroxyacetophenone compounds.

[0245] BA: n-butyl acrylate

[0246] HBA: 4-Hydroxybutyl Acrylate

[0247] AA: Acrylic acid

[0248] NVP: N-vinyl-2-pyrrolidone

[0249] Omnirad184: 1-Hydroxycyclohexyl-phenyl ketone (Omnirad184, manufactured by IGM Resin Co., Ltd.)

[0250] Omnirad651: 2,2-dimethoxy-1,2-diphenylethane-1-one (Omnirad651, manufactured by IGM Resins)

[0251] Omnirad127: 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)2-methylpropan-1-one (Omnirad127, manufactured by IGM Resin Co., Ltd.)

[0252] Omnirad2959: 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylacetone (Omnirad2959, manufactured by IGM Resin Co., Ltd.)

[0253] [Preparation of Photocurable Composition]

[0254] Photocurable compositions C1 to C14 were obtained by mixing the monomer syrup, the crosslinking agent, and the silane coupling agent to form the compositions shown in Table 2 below. 1,9-nonanediol diacrylate (NDDA) was used as the crosslinking agent. An epoxy-containing silane coupling agent (KBM-403 manufactured by Shin-Etsu Silicone Co., Ltd.) was used as the silane coupling agent.

[0255] [Table 2]

[0256]

[0257] [Preparation of adhesive sheet]

[0258] (Manufacturing Example 1: Preparation of Release Liner A)

[0259] 30 parts by weight of addition reaction curing silicone (LTC761 containing hexenyl polysiloxane, 30% by weight toluene solution, manufactured by Dow Corning Toray), 0.9 parts by weight of release control agent (BY24-856 containing unreacted silicone resin, manufactured by Dow Corning Toray), 2 parts by weight of curing catalyst (SRX212 containing platinum catalyst, manufactured by Dow Corning Toray), and a toluene / hexane mixed solvent (volume ratio 1:1) as a diluent were mixed to obtain a silicone release agent composition. The concentration of silicone solid content in the release agent composition was 1.0% by weight. Next, the release agent composition was applied to one side of a liner substrate (Lumirror XD500P as a polyester film, thickness 75 μm) using a wire bar, and heated at 130°C for 1 minute to prepare a release liner A having a release layer (thickness 60 nm) on one side.

[0260] (Manufacturing Example 2: Preparation of Release Liner B)

[0261] A release liner B having a release layer (thickness 120 nm) on one surface was prepared in the same manner as in Production Example 1 except that the thickness of the release agent composition applied to the lining substrate was changed.

[0262] (Example 1)

[0263] The photocurable composition C1 was applied to one side of the release liner A prepared in Production Example 1 using an applicator to form a coating layer. Next, the release liner B prepared in Production Example 2 was arranged on the formed coating layer to obtain a first laminate. Both release liners A and B were arranged so that the release layer and the coating layer were in contact. Next, the coating layer was irradiated at an intensity of 2.5 mW / cm 2, irradiation time 640 seconds, irradiate ultraviolet light (Black light source) from one side of the release liner A in the first stack, so that the coating layer is photocured, forming a second stack consisting of the release liner A, the adhesive sheet (thickness 20μm) and the release liner B. Next, the release liner B is peeled off from the second stack, and the above-mentioned phase difference film, which has been previously corona-treated on both sides, is joined to the exposed surface of the adhesive sheet formed by peeling. Next, another adhesive sheet formed in the same manner as above is joined to the exposed surface of the phase difference film to obtain an optical stack having a stacked structure of release liner A / adhesive sheet / phase difference film / adhesive sheet / release liner A. Next, the release liner A on one side is peeled off from the optical stack, and the polarizing film A or polarizing film B prepared above is joined to the exposed adhesive sheet. The joining is carried out in a manner that the adhesive sheet is in contact with the transparent protective film formed by the modified acrylic polymer in the polarizing films A and B. Thus, an optical laminate A having a laminated structure of polarizing film A / adhesive sheet / phase difference film / adhesive sheet / release liner A (the thickness of the polarizer is 18 μm) and an optical laminate B having a laminated structure of polarizing film B / adhesive sheet / phase difference film / adhesive sheet / release liner A (the thickness of the polarizer is 28 μm) were obtained.

[0264] (Example 2)

[0265] Photocurable composition C2 was used instead of photocurable composition C1, and the surface of each adhesive sheet on the retardation film side was subjected to corona treatment (discharge amount 61 W / (m 2 · points)), an optical layered body A and an optical layered body B of Example 2 were obtained in the same manner as in Example 1.

[0266] (Examples 3 to 10)

[0267] Each optical layered body A and optical layered body B of Examples 3 to 10 were obtained in the same manner as in Example 1 except that each of the photocurable compositions C3 to C11 was used instead of the photocurable composition C1.

[0268] (Example 11)

[0269] Optical layered bodies A and B of Example 11 were obtained in the same manner as in Example 2 except that the photocurable composition C11 was used instead of the photocurable composition C2.

[0270] (Comparative Examples 1 to 4)

[0271] Optical layered bodies A and optical layered bodies B of Comparative Examples 1 to 4 were obtained in the same manner as in Example 1, except that the photocurable compositions C5 and C12-14 were used instead of the photocurable composition C1.

[0272] [Polymerization rate]

[0273] The polymerization rate of each adhesive sheet formed in the embodiment and the comparative example was calculated based on the change in the weight of the adhesive sheet before and after heating and drying at 130°C for 2 hours. Specifically, the weight of the adhesive sheet just after the release liner A and the release liner B were peeled off from the second laminate was set as W0 (weight before drying), and the weight of the adhesive sheet at the time of cooling at room temperature (23°C) for about 20 minutes after the above heating was set as W1 (weight after drying), and the polymerization rate (%) was calculated by the formula: polymerization rate (%) = W1 / W0×100.

[0274] [Amount of residual monomers]

[0275] The amount of residual monomers in each of the PSA sheets formed in the examples and comparative examples was evaluated by GC analysis. The apparatus and measurement conditions used for the GC analysis are shown below.

[0276] · Device used: GC7890A (manufactured by Agilent Technologies)

[0277] Column: HP-1 (manufactured by Agilent Technologies)

[0278] Detector: Flame ionization detector (FID)

[0279] Inlet temperature: 250℃

[0280] · Measurement temperature conditions: The following (1) to (4) were performed in sequence. (1) Keep at 0°C for 3 minutes, (2) Heat at a rate of 10°C / min, (3) After reaching 120°C, heat at a rate of 20°C / min, (4) Keep at 300°C

[0281] Sample preparation method: 0.05 g of the sample (adhesive sheet) was collected in a screw-cap bottle, 2.5 mL of ethyl acetate was added, and the mixture was shaken overnight. The resulting solution was filtered using a 0.45 μm membrane filter, and 1 μL of the filtrate was injected into the GC for analysis.

[0282] [Anchoring force]

[0283] Using each optical laminate A produced in the embodiments and comparative examples, the anchoring force of the adhesive sheet relative to the phase difference film was evaluated by the above method. The double-sided tape used was the trade name "No.531" manufactured by Nitto Denko Corporation. The stainless steel test plate used a SUS304 plate (width 40mm×length 120mm). The evaluation sheet used an ITO film (125Tetoraito OES, manufactured by Oike Industries). The tensile tester used Autograph SHIMAZU AG-I10KN (manufactured by Shimadzu Corporation).

[0284] [Ease of crack formation]

[0285] For each optical laminate A and optical laminate B of the embodiment and comparative example, the susceptibility of cracks in the phase difference film was evaluated as described below. The optical laminate was cut into a rectangle of 300 mm × 210 mm to prepare a test piece. Next, the release liner A was peeled off, and the test piece was attached to the surface of the glass plate via the adhesive sheet exposed by peeling. Next, heating was performed in an autoclave at 50°C for 15 minutes, thereby stabilizing the bonding between the test piece and the glass plate, and a sample for evaluation was obtained. For the obtained samples, repeated thermal shock tests at -40°C and 85°C were performed, and the presence or absence of cracks in the phase difference film after 100, 200 and 300 thermal cycles were confirmed by an optical microscope. Three samples were prepared for each optical laminate, and the susceptibility of cracks in the phase difference film was evaluated according to the number of samples with cracks. The conditions of the thermal cycle are as follows.

[0286] One cycle: after leaving it in an atmosphere of -40°C for 30 minutes, leaving it in an atmosphere of 85°C for 30 minutes.

[0287] The evaluation results are shown in the following Table 3. It should be noted that the "corona treatment" in Table 3 refers to the corona treatment of the adhesive sheet. The amount of residual monomers shown in Table 3 is the total amount of residual monomers in all adhesive sheets contained in the optical laminate of the evaluation object. In the "Ease of Cracks" column, the number of samples that cracked among the three samples evaluated is set to n, and recorded as "n / 3".

[0288] [Table 3]

[0289]

[0290] Industrial Applicability

[0291] The optical layered body of the present invention can be used in, for example, an image display device.

Claims

1. An optical laminate comprising: An adhesive sheet formed from a photocurable composition containing a monomer group and / or a partial polymer of the monomer group, and Retardation film, The adhesive sheet is in contact with the phase difference film directly or via a layer having a thickness of 10 μm or less. The amount of residual monomers contained in the pressure-sensitive adhesive sheet is 16000 ppm (weight basis) or less.

2. The optical layered body according to claim 1, wherein: The optical laminate includes the two pressure-sensitive adhesive sheets disposed so as to sandwich the retardation film.

3. The optical layered body according to claim 1, wherein: The optical laminate comprises two or more adhesive sheets. The total amount of the residual monomers contained in the two or more PSA sheets is 16000 ppm (weight basis) or less.

4. The optical laminate according to claim 1, wherein: The optical laminate further includes a polarizing film.

5. The optical layered body according to claim 4, wherein: The polarizing film and the phase difference film sandwich the adhesive sheet.

6. The optical layered body according to claim 1, wherein: The monomer group includes a (meth)acrylic monomer.

7. The optical layered body according to claim 1, wherein: The monomer group includes a carboxyl group-containing monomer.

8. The optical layered body according to claim 7, wherein: The content of the carboxyl group-containing monomer in the monomer group is 4.5% by weight or more.

9. The optical layered body according to claim 1, wherein: The monomer group includes nitrogen atom-containing monomers.

10. The optical layered body according to claim 1, wherein: The photocurable composition comprises a photopolymerization initiator, The photopolymerization initiator is a compound having a chemical structure represented by the following formula (1) in the molecule, R of the formula (1) 1 and R 2 Each independently is a C1-C8 alkyl group; the hydrogen atom is replaced by -OH, C1-C4 alkoxy, -CN, -COOR 51 、-OOCR 52 or -NR 53 R 54 Substituted C1-C4 alkyl; C3-C6 alkenyl; or -CH2-C6H4-R 55 , R 1 and R 2 They are optionally bonded to each other to form a C2-C9 alkylene group, a C3-C6 oxyalkylene group, or an azaalkylene group, X is -OR 56 , or -NR 57 R 58 , R 51 is a C1-C8 alkyl group, R 52 is a C1-C4 alkyl group, R 53 and R 54 Each independently represents a hydrogen atom, a C1-C12 alkyl group; the hydrogen atom is selected from -OH, a C1-C4 alkoxy group, -CN and -COOR 59 At least one of the groups is substituted with a C2-C4 alkyl group; a C3-C5 alkenyl group; or a cyclohexyl group, R 53 and R 54 are optionally bonded to each other and optionally substituted by -O- or -N(R 60 )-interrupted C3-C9 alkylene, R 55 is a C1-C4 alkyl group, R 56 is a hydrogen atom, -SiR 62 3. C1-C8 alkyl, or C3-C6 alkenyl, R 57 and R 58 is a C1-C12 alkyl group; the hydrogen atom is selected from -OH, C1-C4 alkoxy, -CN and -COOR 63 At least one of the groups is substituted with a C2-C4 alkyl group; a C3-C5 alkenyl group; or a cyclohexyl group, R 57 and R 58 are optionally bonded to each other and optionally substituted by -O- or -N(R 64 )-interrupted C3-C9 alkylene, R 59 is a C1-C4 alkyl group, R 60 is a hydrogen atom, a C1-C4 alkyl group, an allyl group, a C1-C4 hydroxyalkyl group, -CH2CH2-COOR 61 or -CH2CH2CN, R 61 is a C1-C4 alkyl group, R 62 is a C1-C6 alkyl group, R 63 is a C1-C4 alkyl group, R 64 is a hydrogen atom, a C1-C4 alkyl group, an allyl group, a C1-C4 hydroxyalkyl group, -CH2CH2-COOR 65 or -CH2CH2CN, R 65 is a C1-C4 alkyl group, The chemical structure can be bonded to a hydrogen atom or a substituted structure of a hydrogen atom via the carbon atom represented by * in the formula (1).

11. The optical laminate according to claim 1, wherein: The photocurable composition includes a first photopolymerization initiator having a relatively small first reaction rate and a second photopolymerization initiator having a relatively large second reaction rate. The ratio of the second reaction rate to the first reaction rate, represented by the ratio of the polymerization rates A evaluated by the following measurement method using only the respective photopolymerization initiators, is 1.1 or more. Determination method: A mixed solution of 99 parts by weight of n-butyl acrylate and 1 part by weight of 4-hydroxybutyl acrylate as monomers and 0.1 parts by weight of a photopolymerization initiator to be evaluated was irradiated with ultraviolet rays to prepare a monomer slurry in which the monomers were partially polymerized; the ultraviolet irradiation was carried out until the viscosity of the mixed solution at 30° C. reached 20 Pa·s; then, a coating layer with a thickness of 20 μm formed by the prepared monomer slurry was formed between a pair of polyethylene terephthalate (PET) sheets each having a thickness of 75 μm; then, the coating layer was irradiated with ultraviolet rays using an LED having a peak wavelength of 340 nm±10 nm as a light source from one side of the PET sheet; the irradiation ultraviolet light intensity and irradiation time were set to 4 mW / cm 2 and 1200 seconds; the polymerization rate of the monomer measured on the coating layer after photocuring by irradiating the ultraviolet rays is determined as the polymerization rate A.

12. The optical layered body according to claim 1, wherein: The adhesive sheet has a surface to which a surface modification treatment has been applied.

13. The optical layered body according to claim 1, wherein: The thickness of the adhesive sheet is 50 μm or less.

14. The optical layered body according to claim 1, wherein: The adhesive sheet has an anchoring force of 13 N / 25 mm or more with respect to the phase difference film. 15 . An image display device comprising the optical layered body according to claim 1 .

Citation Information

Patent Citations

  • Optical display device having polarizing film

    JP2012133303A

  • Ultraviolet-curable acrylic adhesive composition, ultraviolet-curable acrylic adhesive layer, polarization film with adhesive layer, method for producing ultraviolet-curable acrylic adhesive layer and image display device

    JP2016155981A